2021
DOI: 10.3390/polym13234182
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Blended Bombyx mori Silk Fibroin and Recombinant Spider Silk Fibroin Hydrogels on Cell Growth

Abstract: Binary-blended hydrogels fabricated from Bombyx mori silk fibroin (SF) and recombinant spider silk protein eADF4(C16) were developed and investigated concerning gelation and cellular interactions in vitro. With an increasing concentration of eADF4(C16), the gelation time of SF was shortened from typically one week to less than 48 h depending on the blending ratio. The biological tests with primary cells and two cell lines revealed that the cells cannot adhere and preferably formed cell aggregates on eADF4(C16)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…For instance, SF hydrogels were shown to support L929 proliferation, but at a slower rate than TCP. 69 Higher SF content correlates to higher rates of fibroblast proliferation due to the presence of growth-promoting polypeptides in the N-terminal region of the fibroin polypeptide. Fibroblasts on SF-glycerol films suggested that less-favorable, early-stage fibroblast adhesion and growth stems from silk's hydrophobic domains and lack of surface topography.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, SF hydrogels were shown to support L929 proliferation, but at a slower rate than TCP. 69 Higher SF content correlates to higher rates of fibroblast proliferation due to the presence of growth-promoting polypeptides in the N-terminal region of the fibroin polypeptide. Fibroblasts on SF-glycerol films suggested that less-favorable, early-stage fibroblast adhesion and growth stems from silk's hydrophobic domains and lack of surface topography.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Substrates supported cell proliferation, with cell number logarithmically increasing over 7 days, in agreement with previous findings. For instance, SF hydrogels were shown to support L929 proliferation, but at a slower rate than TCP . Higher SF content correlates to higher rates of fibroblast proliferation due to the presence of growth-promoting polypeptides in the N-terminal region of the fibroin polypeptide.…”
Section: Resultsmentioning
confidence: 99%
“…The study also confirmed calcium production through alizarin red staining. Importantly, this study reveals that hydrogels can carry drugs and cells efficiently with their functionalities intact [173] .…”
Section: Sf Hydrogel As Delivery Vehiclementioning
confidence: 85%
“…[ 11 ] The ability of fulling irregular shaped defects makes injectable materials can conform to the shape and size of the bone defect, providing a customized fit that can improve the effectiveness of the treatment. [ 5 ] Moreover, they can promote the recruitment and proliferation of bone‐forming cells, [ 12 ] accelerate the formation of new bone tissue, and enhance the integration of the implant with the surrounding bone. [ 13 ]…”
Section: Introductionmentioning
confidence: 99%